PREVALENSI, FAKTOR RISIKO DAN DERAJAT HELMINTHIASIS PADA SAPI LIMOUSIN DI BPTU-HPT PADANG MENGATAS - Habib, Afifah Arini; Arif, Ridi; Ridwan, Yusuf (JURNAL KAJIAN VETERINER, 2022)
Helminthiasis is a disease caused by the infection of helminth parasite which is responsible for loss of livestock productivity. The cross-sectional study was conducted to determine the prevalence rate, degree infection, and risk factors for helminthiasis in limousine cattle at Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) PadangMangatas. Fecal were collected and examined qualitatively by sedimentation and floatation methods andquantitatively by the McMaster method. Secondary data of helminthiasis cases in limousine cattle during the last three years 2018-2020 was collected from BPTU-HPT Padang Mangatas surveillance record. Limousine cattle at BPTU-HPTPadang Mangatas have a high prevalence of helminthiasis. Overall, the prevalence of gastrointestinal (GI) infection was 66.67 % and the eggs identified were Strongyle type egg (64.81%) and Moniezia benedeni. (12.96%). The prevalence ofinfection in cattle above 2 years old (0%) was significantly lower (P<0.001) than calves under 8 months of age (84.37%), and between 8-24 months of age (81.82%). The geometric mean of TTGT values shows the degree of helminth infection is relatively low (<500 TTGT).